Implementasi Joyful Learning dalam Meningkatkan Partisipasi Siswa pada Pembelajaran Ekonomi - Syata, Wahyu Muh. (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyze the implementation of joyful learning in increasing student participation in economics education. The research uses a Systematic Literature Review (SLR) approach by examining various relevant scientific articles from the period 2017–2025. Data were obtained thru searches of academic databases such as Google Scholar, Scopus, and national journals, and then analyzed using content analysis techniques and descriptively synthesized. The research results show that the implementation of joyful learning can significantly increase student participation, both cognitively, emotionally, and socially. This approach is effective because it integrates a pleasant learning atmosphere, contextual presentation of materials, and active student involvement in the learning process. The application of strategies such as digital media, gamification, group discussions, and collaborative activities has proven to enhance students' motivation, concentration, creativity, and confidence. In addition, joyful learning also contributes to creating an interactive and student-centered learning environment. However, the success of its implementation is influenced by the competence of teachers, the availability of infrastructure, and the support of educational policies. Therefore, the joyful learning approach has become one of the relevant learning strategies to enhance student participation and the quality of economic education sustainably.